Pengembangan Fukien Ikan Kembung Banjar dengan Substitusi Tepung Talas Belitung (Xanthosoma sagittifolium): Analisis Sensori, Preferensi Konsumen, dan Rintisan Usaha - Wahyu Pamungkas; Handoko Handoko; Mutia Vanessia; Annis Kandriasari; Efrina Efrina (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
This study aims to evaluate the sensory quality, consumer acceptability, and business feasibility of a novel fukien product made from Banjar mackerel and partially substituted with Belitung taro flour (Xanthosoma sagittifolium), named "Fukimpul." Sensory quality tests were conducted using organoleptic and hedonic assessments on three substitution levels (20%, 30%, and 40%) for parameters such as internal color, mackerel taste, taro taste, umami flavor, fresh mackerel aroma, taro aroma, and texture. The 20% substitution level yielded the highest overall scores in sensory evaluation and consumer preference tests involving 100 panelists. Based on these findings, a start-up business model was developed using a pre-order production system and social media-based distribution. A qualitative descriptive approach was applied to analyze market potential, production design, organizational structure, and financial viability. The results demonstrate that Fukimpul has strong market competitiveness, favorable consumer responses (with a Customer Satisfaction Index of 97.1%), and a break-even point projected at 10.7 months. The study concludes that a 20% substitution of Belitung taro flour provides the best sensory and acceptability outcomes and recommends Fukimpul as a practical, nutritious, and scalable ready-to-cook product for sustainable local entrepreneurship.